Design of an Online Monitoring System for Combustion Field Parameter in a Furnace Based on Tunable Diode Laser Absorption Spectroscopy Technology - LI Yuan; GUO Zhicheng; MENG Xiaochao; CHEN Kefeng; REN Liming; MAO Rui; CEN Kefa (发电技术, 2022)
Based on the tunable diode laser absorption spectroscopy (TDLAS) technology, one-dimensional and multi-dimensional combustion parameter monitoring systems were designed to simultaneously monitor multiple combustion field parameters in the furnace (such as temperature, CO, CO2, and NO concentration, etc.). In the one-dimensional system, the optical switch technology was applied to measure the multiple combustion parameters simultaneously. In the two-dimensional system, the spectrometer technology and algebraic reconstruction technique (ART) were introduced to inversion calculate and measure the two-dimensional combustion parameters in a layer. On this basis, the three-dimensional system was designed. The measurement procedures of three-dimensional combustion parameters were as follows: the combustion region in the furnace was divided into multilayer sections; the two-dimensional combustion parameters were reconstructed based on ART; the three-dimensional combustion parameters were reconstructed using the multilayer combustion parameter data. The combustion filed parameter monitoring system contributes to the fine combustion adjustment in the future.